Uji Efektivitas Pestisida Nabati Daun Mengkudu Terhadap Pengendalian Penyakit Antraknosa Pada Tanaman Cabai - Hairu Suparto; Akhmad Gazali; Antar Sofyan; Risma Nur Hikmah; Ici Piter Kulu (Jurnal Penelitian UPR, 2023)
Anthracnose is a disease that attacks and is very feared in chili cultivation. The low production and productivity of chili plants is caused by this disease. The purpose of this study was to determine the effectiveness and concentration of noni leaf pesticides on the control of anthracnose. This research was arranged using a completely randomized design (CRD) with one factor, namely the treatment of giving concentrations of vegetable pesticides and noni. The treatment consisted of 6 levels of treatment, namely DM0 = Control (0 ml Noni leaf extract solution), DM1 = Noni leaf extract solution 5 g/100 ml water, DM2 = Noni leaf extract solution 10 g/100 ml water, DM3 = Leaf extract solution noni 15 g/100 ml water, DM4 = Noni leaf extract solution 20 g/100 ml water, FS = synthetic fungicide as positive control. The experiment was carried out 4 times, so that 24 experimental units were obtained. The results showed that noni leaf pesticides were effective in controlling anthracnose in cayenne pepper plants with an effective concentration found in DM4 treatment with 20 g/100 ml of water extract solution of noni leaf.